Recent Advances in Solar Drying of Agricultural Produce in Nigeria: NSPRI Experience - Ade, A. R.; Olayemi, F. F.; Adebiyi, A. O.; Zubair, O. M.; Adeiza, O. A.; Achime, K. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Agricultural products are dried to enhance storage stability, in order to reduce post harvest losses, minimize packaging requirement and reduce transport weight. Crop drying through the sun is the most common practice in the country due to its no energy cost but often result in poor quality, unhygienic and contaminated products. This has been a major threat to food safety. Energy consumption and quality of dried products are critical parameters in the selection of drying process. An optimum drying system for the preparation of quality dehydrated products is supposed to be cost effective with less drying time and damage to the product. To reduce the energy utilization and operational cost as well to further produce high quality safe products, new trends in solar drying system were developed by the Nigerian Stored Products Research Institute (NSPRI) in order to proffer solutions to the threat in food safety as well as farmers and processors quest for drying with minimal energy cost. The technologies include mobile solar tent dryers, green house solar tent dryers and parabolic solar tent dryers. These entire dryers have great scope for the production of quality dried products and powders. These advancements have taken the advantage of material selection, design calculations to improve on the technology in order to achieve quality output in terms of environmental parameters and product quality. The advancement has also taken care of times of low solar irradiance especially during the rainy season which is highly humid. The temperature range obtained from the mobile, green house and parabolic solar dryers are 20 – 59.5°C, 21.5 - 68°C, and 25-78°C respectively while their respective average relative humidity are 71.64%, 60.21%, 49.77%. The ambient temperature range and relative humidity are 20 – 42.5°C and 74.88%. Experimental studies on the performance of the varied solar tent dryers were conducted using Chilli Pepper, Yam, Meat, Fish, Vegetables and plantain have been carried out the Beef meat, Chilli pepper and Telefeiria occidentalis vegetable were dried in the mobile solar tent dryer, greenhouse solar dryer and parabolic solar dryer. The beef of 71.243% initial moisture content was dried to 12.15%, 12.01% and 10.09% in the aforementioned respective dryers within a period of 5 days. Also the chilli pepper of 89.40% initial moisture content was dried to 12%, 11.3% and 9.3% moisture content respectively in the dryers within a period of 8 days; while the Telefairia occidentalis vegetable of 11.0% initial moisture content was dried within a period of 5 hours to 6.0%, 5.5% and 4.0% moisture content.